5/3(2x-6)+18=2/3(x+3)-4

Simple and best practice solution for 5/3(2x-6)+18=2/3(x+3)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5/3(2x-6)+18=2/3(x+3)-4 equation:



5/3(2x-6)+18=2/3(x+3)-4
We move all terms to the left:
5/3(2x-6)+18-(2/3(x+3)-4)=0
Domain of the equation: 3(2x-6)!=0
x∈R
Domain of the equation: 3(x+3)-4)!=0
x∈R
We calculate fractions
(15xx/(3(2x-6)*3(x+3))+(-6x2/(3(2x-6)*3(x+3))+18=0
We can not solve this equation

See similar equations:

| 4r+19=19 | | 2=11-3q | | 6+n.5=-4 | | 15=5+2f | | 5d–2(6d–1)=-12 | | -9=v/4 | | 12=s+3 | | 4x=1x-12 | | 3(c+1)=12 | | t/2+6= 8 | | 200m-125m+42,125=46,125-150m | | 16=s+13 | | t2+6= 8 | | X+3(x+2)=5(x-4)+16 | | 2y+y-6=180 | | -4y-19=-19 | | 6x-68=2x-24 | | t/2+ 6= 8 | | t2+ 6= 8 | | (x-2)^2=28 | | n^2-8n-54=-6 | | (8x-3)^2-2=-1 | | x^2+20x+47=-4 | | b/17+4=9 | | 3(x-2)^2+5=32 | | 16=7+3k | | (8x-3)^2=-1 | | 5−4+7x+1=5-4+7x+1=0x+2 | | 4(x+3)–5=47 | | 14=3r+2 | | 3x+2(x-17)=6 | | Y=-x^2+5x-3 |

Equations solver categories